2000
DOI: 10.1038/35019066
|View full text |Cite
|
Sign up to set email alerts
|

State-dependent cross-inhibition between transmitter-gated cation channels

Abstract: Transmitter-gated cation channels are detectors of excitatory chemical signals at synapses in the nervous system. Here we show that structurally distinct alpha3beta4 nicotinic and P2X2 channels influence each other when co-activated. The activation of one channel type affects distinct kinetic and conductance states of the other, and co-activation results in non-additive responses owing to inhibition of both channel types. State-dependent inhibition of nicotinic channels is revealed most clearly with mutant P2X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
118
2
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(136 citation statements)
references
References 27 publications
15
118
2
1
Order By: Relevance
“…Application of ATP did not gate or modulate GABA C receptors, and GABA did not activate or modulate P2X 2 receptors, showing that nonspecific cross-activation or cross-desensitization between one type of transmitter and the other type of receptor could not explain the cross-inhibition observed during co-application. A similar reciprocity of cross-inhibition was observed between P2X 2 and nicotinic or 5-HT 3 receptors (24,26). Interestingly, an inhibitory cross-talk between P2X and GABA A channels reported in dorsal root ganglion neurons indicates a more pronounced inhibitory effect of GABA receptors on P2X channels than the reverse (25).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Application of ATP did not gate or modulate GABA C receptors, and GABA did not activate or modulate P2X 2 receptors, showing that nonspecific cross-activation or cross-desensitization between one type of transmitter and the other type of receptor could not explain the cross-inhibition observed during co-application. A similar reciprocity of cross-inhibition was observed between P2X 2 and nicotinic or 5-HT 3 receptors (24,26). Interestingly, an inhibitory cross-talk between P2X and GABA A channels reported in dorsal root ganglion neurons indicates a more pronounced inhibitory effect of GABA receptors on P2X channels than the reverse (25).…”
Section: Discussionsupporting
confidence: 49%
“…Functional cross-inhibition between receptors activated by ATP and either acetylcholine or GABA has been reported lately in neurons or transfected cells (21)(22)(23)(24)(25), and we recently demonstrated that a physical interaction between P2X and 5-HT 3 receptors leads to an activity-dependent cross inhibition between the two cationic channels (26). We decided to explore the possibility that ligandgated chloride channels may also interact with P2X ATP-gated channels through similar mechanisms.…”
mentioning
confidence: 99%
“…4C). T18A mutant receptors are useful because they allow P2X 2 receptor responses to be assigned to a particular channel state, and we interpret the rapid desensitization kinetics in T18A mutants as indicative of the presence of only the I 1 state (23). Overall these data imply that P2X 2 -GFP receptor redistribution and varicosity formation require prolonged P2X 2 receptor function, for instance, as produced by the I 2 state.…”
Section: Materials and Methods)mentioning
confidence: 81%
“…10). There is evidence for direct protein-protein interactions (cross-talk) between the intracellular domains of different channels in close proximity (15,16). It is possible that GABARAP, by aggregating receptors, promotes interaction(s) between the intracellular domains of the closely packed receptors so that several pentameric channels open cooperatively.…”
Section: Discussionmentioning
confidence: 99%